Conceptualizing and encoding motion in Turkish and Croatian: polysemy of verbs çikmak and izaći - Kerovec, Barbara (2008)
Following the experiential approach to meaning, the paper examines the semantic structures of the two polysemous verbs of directional motion: Turkish verb çikmak („ exit“ , „ go/come out“ ; „ ascend“ , „ climb up“ , „ go up“ ) and Croatian verb izaći („ exit“ , „ go/come out“ ). The focus is placed on the way the motion is conceptualized and linguistically encoded in the two typologically distinct languages. Turkish, as a verb-framed language, encodes the path of motion in the main verb, while Croatian, as a satellite-framed language, encodes the path in prefixes and prepositions. The results show that although conceptualization of basic space relations and motion is the same in the two languages, their typological properties make them differ in expressing manner of motion. In Croatian, as the path of motion is encoded in prefixes, the main verb slot stays available for manner verb, which results with greater lexical diversity expressing manner in Croatian in contrast to Turkish. This can be remarked in lexical encoding of concrete as well as of abstract meanings of the two chosen verbs. The very majority of the semantic equivalents of the Turkish verb çikmak in Croatian cannot be encoded simply by the lexical item izaći, but rather by various manner verbs mostly preceded by the prefixal morpheme iz-, carrying the meaning of the particle out in English. This difference holds particularly for those meanings that include suddenness, quickness or vehemence: while these can be expressed in Turkish by the verb çikmak, Croatian verb izaći carries rather manner-neutral meanings. Accordingly, Turkish verb çikmak has greater diversity of use than Croatian verb izaći. Also, as Turkish and Croatian are languages deriving from different cultures, some cultural differences in the use of the chosen verbs can be noticed.
Projekt MZOS
ENG